PENINGKATAN INTERAKSI EDUKATIF DAN HASIL BELAJAR DENGAN TIPE MAKE A MATCH DI KELAS IV - W, Syarifah Desi; Marli, Suhardi; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe formulation of the problem in this study is an increase in educational interactions and student learning outcomes by using the type of Make A Match in class IV Public Elementary School 13 East Pontianak. The research used is descriptive method, while the form of research used is classroom action research with the nature of collaborative research. Subjects in the study were 28 students in class IV. Data collection techniques used are direct observation and documentation techniques. Data collection tool used in the form of research results sheets. This sub-study is the IV kevasah students of the State Elementary School 13 East Pontianak who have 28 students. This research was carried out as many as 3 cycles with the results of the first average teacher's ability to plan learning as follows in cycle I 2.75 in cycle II 3.00 in cycle III 3.65. The average ability of teachers to carry out learning in cycle I 2.32 in cycle II 3.33 in cycle III 3.55. The average of educational interactions in the first cycle was 14.28%, in the second cycle 28.58%, and in the third cycle 42.85%. Student learning in cycle I with an average of 61.07, in cycle II students with an average of 70.00, and in cycle III with an average of 79.64.Thus it can be concluded that using the Make A Match type in Social Science learning can increase educational interactions and student learning outcomes in class IVA 13 Pontianak Timur Elementary School. Keywords: Increased Educational Interactions Learning Outcomes Make A Match